Use of liquid chromatographic methods for gelatin differentiation in halal verification - Mohd Ismail, Azilawati; Ismail, Amin; Bakar, Jamilah; Mustafa, Shuhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
A wide diversity of gelatin sources that supported by the largest scale of porcine gelatin production in a global market has raised doubts among Muslim consumers towards gelatin-based ingredients products. The skepticism has been addressed through the implementation of food labelling regulations that require manufacturers to state the source of gelatin on the packaging. Since the application of halal certification is voluntary and not compulsory for industry players, hence it gives significant drawbacks. Without strictly monitoring and enforcement, the probability of contamination with non-halal materials during the production process and lacking of halal integrity particularly in the supply chain of raw materials may increase the number of masbooh and non-compliance products according to the Islamic law. Therefore, a trust on the halal products must be strengthened with the scientific evidence. This paper attempts to critically review on liquid chomatographic methods in determining the species origin of gelatin. It covers series of technological changes from a simple of high performance liquid chromatography (HPLC) to the system that coupled with mass spectrometry. A large similarity in amino acids profile and polypeptide sequences of the mammalian gelatin will be the main challenge in developing the analytical methods. Matrix interference in the gelatin-based products, adulteration and fraud in the mixed ingredients are an inevitable, hence it need to be tackled and solved. These analytical methods are expected to be used as tools to provide scientific evidences for halal verification on the gelatin-based products.